+0  
 
0
22
2
avatar+4 

Compute $15^2- (37^2 - 33^2 - 15)^2 $. I am getting -70,000

 Jun 6, 2023
 #1
avatar
0

We can compute this expression as follows:

15^2- (37^2 - 33^2 - 15)^2 = 225 - (1369 - 1089 - 15)^2 = 225 - (280)^2 = 225 - 78400 = -78175

Therefore, the answer is −78175.

 Jun 6, 2023
 #2
avatar
0

15^2- (37^2 - 33^2 - 15)^2

 

1 - Calculate the numbers in parenthesis first:

15^2 - (1369 - 1089 - 15)^2 

 

2 - 15^2 - ( - 1369 + 1089 + 15)^2

 

3 - 15^2 -  265^2

 

4 - 225 - 70225

 

5 - = - 70,000 - which is same as you got.

 Jun 6, 2023

7 Online Users